2021
DOI: 10.1021/acs.langmuir.1c01338
|View full text |Cite
|
Sign up to set email alerts
|

Model Asphaltenes Adsorbed onto Methyl- and COOH-Terminated SAMs on Gold

Abstract: Petroleum asphaltenes are surface-active compounds found in crude oils, and their interactions with surfaces and interfaces have huge implications for many facets of reservoir exploitation, including production, transportation, and oil−water separation. The asphaltene fraction in oil, found in the highest boiling-point range, is composed of many different molecules that vary in size, functionality, and polarity. Studies done on asphaltene fractions have suggested that they interact via polyaromatic and heteroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The primary purpose of the QCM study was to see if different measurement methods of determining asphaltene adsorption/ deposition would yield similar conclusions with respect to surface modification. For this study, three gold/quartz crystals were first functionalized with three different end-functionalized thiol SAMs, following the method suggested recently by Girard et al 21 and Golbek et al 56 The hydroxyl-terminated SAM mimics untreated silica, while the methyl-and fluorineterminated SAMs mimicked the alkane and perfluorinated modifications used in the adsorption and deposition studies. The three different modified gold/quartz sensors were immersed in solutions of various concentrations of asphaltene in the toluene/tetradecane solvent and measurements recorded of the added mass over time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The primary purpose of the QCM study was to see if different measurement methods of determining asphaltene adsorption/ deposition would yield similar conclusions with respect to surface modification. For this study, three gold/quartz crystals were first functionalized with three different end-functionalized thiol SAMs, following the method suggested recently by Girard et al 21 and Golbek et al 56 The hydroxyl-terminated SAM mimics untreated silica, while the methyl-and fluorineterminated SAMs mimicked the alkane and perfluorinated modifications used in the adsorption and deposition studies. The three different modified gold/quartz sensors were immersed in solutions of various concentrations of asphaltene in the toluene/tetradecane solvent and measurements recorded of the added mass over time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A discussion on surface passivation of graphene with PDs has been reported elsewhere . To reach at least about 90% surface coverage by a monolayer of PDs and to avoid the formation of dimers or trimers, surfaces of the sensors were rinsed with a compatible solvent. , Table shows the specific information on the PDs and corresponding solvents used in this work.…”
Section: Materials and Experimental Designmentioning
confidence: 99%
“…The COOH-SAM surface [isoelectric point (IEP) is about 2.9, Figure S2] exhibits different surface charge densities under different pH values . It is reported that SAM-COOH has no significant molecular orientation since it can be both donor and acceptor for the hydrogen bonding to form dimeric species. The results show that the introduction of ions increases the oil adhesion compared to pure water, which is attributed to disruption of the orderliness of the interfacial water. The efficiency of ions in regulating oil adhesion follows the Hofmeister series and is related to the ion valence.…”
Section: Introductionmentioning
confidence: 99%